"It Makes My Skin Crawl": Women's experience of breastfeeding aversion response (BAR). Issue 6 (November 2022) - Morns, Melissa A.; Steel, Amie E.; McIntyre, Erica; Burns, Elaine
Abstract: Problem: Some women who intend to breastfeed experience a breastfeeding aversion response (BAR) while breastfeeding. Background: Little is known about the experience of those who have feelings of aversion while breastfeeding. Aim: This study aimed to investigate the experiences of women who have an aversion response to breastfeeding while their infant is latched at the breast. This is the first study that aims to understand this breastfeeding aversion response (BAR) as described by women who experience this phenomenon. Methods: Interpretative phenomenological analysis (IPA) was used to conduct and analyse ten semi-structured in-depth interviews with women who self-identified as experiencing BAR. Findings: Four overarching themes were identified: (1) Involuntary, strong sensations of aversion in response to the act of breastfeeding, (2) Internal conflict and effects on maternal identity, (3) The connection between BAR and relationships with others, and (4) Reflections on coping with BAR and building resilience. Discussion: Some women who intend to breastfeed can experience BAR, and this negative sensation conflicts with their desire to breastfeed. BAR can impact on maternal wellbeing. Those who experience BAR may benefit from person-centred support that directly addresses the challenges associated with BAR to achieve their personal breastfeeding goals. Conclusion: The experience of BAR is unexpected and difficult for mothers. If support is not available, BAR can have detrimental effects on maternal identity, mother–child bonds, and intimate family relationships.